HOW TEACHERS TEACH AND HOW STUDENTS PERCEIVE TEACHING WRITING RECOUNT TEXTS USING WEBBING TECHNIQUE:A Quasi-Experimental Study of the Second Grade Students at one SMP in Bandung - Feby Andryani, - (2012)
The present study investigated the use of webbing technique to improve students' skill in writing recount text and identify the students' perception towards the use of webbing technique in teaching writing recount text. Webbing was chosen because it is one of the outlining techniques which leads the students to find out more easily main idea to start writing. The study employed quasi-experimental design in one Junior High School in Bandung. Two classes, each of which consists of 30 students, were selected as the control group and the experimental group.The data gathered through pre-test and post-test was computed by using SPSS Statistics 17.0 for Windows while data from questionnaire were analyzed based on the frequency students' answers and then were calculated and interpreted into percentages. The result of the study shows that webbing technique effective in improving students' writing skill (t obt 5.069 > tcrit 2.000) and there is significant difference of means scores in post test of both experimental and control groups where post test score of experimental group is 61.17 and control group is 41.43. Moreover, the questionnaire result shows the positive perception from the students towards the use of webbing technique in writing recount text where 96.7% of the students agree that webbing technique improves their writing skill and only 26.7% of them found that webbing is not useful. Thus, 90% of the students want to keep this technique in writing recount text. However, it is better if future researchers conducted this study in the form of true experimental designs and implement webbing combined with other techniques.